Hubungan Faktor Individu Dengan Pengetahuan Orang Tua Siswa Tentang Kelainan Refraksi Pada Anak Di MIS Al-Mubarak - Imam Nawawi; Ulfah Rimayanti; Andi Irhamnia Sakinah (Jurnal Kesehatan Panrita Husada, 2023)
Refractive disorders are conditions when the image of an object does not form perfectly on the retina due to abnormalities in the eye's optical system, so that vision becomes blurred. The role of parents is very important in detecting refractive errors in children so that prevention can be done more quickly. The aim of this research was to determine the relationship between individual factors and parents' knowledge about refractive errors in children at Al-Mubarak Private Madrasah Ibtida'iyah. This research is quantitative research with an analytical survey method; namely, the researcher only makes direct observations of the variables studied without providing treatment. This research was designed with a cross-sectional study approach. Correlation tests using the Spearman test and the Eta Correlation test did not show a significant correlation in the variables age, gender, education, income and occupation with a P-value > 0.05. Meanwhile, for the information source variable, significant results were obtained with a p-value of 0.000 (<0.05).